A comparison of behavioural models explaining cervical cancer screening uptake - Jyoshma Preema Dsouza; Stephan Van den Broucke; Sanjay Pattanshetty; William Dhoore (BMC, 2022)
Abstract Background Cervical cancer represents a very high burden of disease, especially in Low- and Middle-income economies. Screening is a recommended prevention method in resource-poor settings. Cervical cancer screening (CCS) uptake is influenced by various psycho-social factors, most of which are included in behavioural models. Unlike demographic characteristics, these factors are modifiable. While few studies have compared these models in terms of their capacity to predict health behaviour, this study considers three health behaviour theories to assess and compare the predictors of CCS behaviour and intention. Methods A survey was conducted among 607 sexually active women in the South Indian state of Karnataka. Data was collected regarding socio-demographic factors, health literacy, knowledge on CCS, and the socio-cognitive factors related to CCS that are represented in the Health Belief Model (HBM), Theory of Planned Behaviour (TPB) and Theory of Care-Seeking Behaviour (TCSB). Logistic regression analyses tested to what extent each of the theoretical models explained cervical cancer screening (CCS) intention and regular screening behaviour, comparing the variance explained by each of the models. Results CCS intention was best explained by the TPB, followed by the HBM. Of the constructs included in these models, positive attitude towards the screening procedure and perceived benefits contributed most significantly to screening intention, followed by fear, anxiety or embarrassment related to the disease or screening procedure, and context specific barriers. Conclusion Health behavioural models such as the TPB and HBM can help to identify the main socio-cognitive factors explaining the intention of women to participate in CCS. As such, they can inform interventions to target specific determinants of screening intention and behaviour, and enhance their effectiveness by addressing women's screening attitude, perceived benefits, and emotions as well as reducing context specific barriers to screening.